Peran Kepala Sekolah Dalam Meningkatkan Motivasi Kerja Guru di SDN 06 Cakranegara - Susilawati, Nurul Aslina; Witono, A. Hari (Magister Pendidikan Dasar FKIP Universitas Mataram, 2024)
This study aims to describe the role of the head of a school as a motivator in increasing teachers' work motivation, an overview of teachers' work motivation and factors that affect the role of school principals in increasing teachers' work motivation. Research method with a descriptive approach. Data collection techniques include interviews, observations, and documentation, with data analysis techniques in the form of data reduction, data presentation/display, and data verification with conclusions. The results obtained in this study show that; 1) the role of the principal as a motivator, arranging a conducive work environment, regulating a comfortable working atmosphere, applying the principles of reward and punishment, and encouraging teachers to develop their careers.